Managing electronic resources in libraries: issues and challenges (2011)
Electronic resources are increasingly being found in libraries. The management of the e-resources involves acquisition, cataloguing and classification and also providing access to them. Ways in which e-resources are managed are discussed pointing out the role of staff and users in the management chain. An online survey of librarians' knowledge of electronic resources and the use of electronic resources management software was conducted. Results from the survey reveal that quite a number of librarians are unaware of Electronic Resources Management Systems (ERMS) in their libraries, and managing e-resources in most of the libraries is deemed difficult. Various issues affecting ability of libraries to manage their e-resources and the challenges that have to be faced in the organization process are highlighted. Recommendations are made of the way forward for librarians and libraries to follow established guidelines and learn from other libraries that have success stories in e-resources management.